2020
DOI: 10.1002/pro.3878
|View full text |Cite
|
Sign up to set email alerts
|

Deuteration of nonexchangeable protons on proteins affects their thermal stability, side‐chain dynamics, and hydrophobicity

Abstract: We have investigated the effect of deuteration of non‐exchangeable protons on protein global thermal stability, hydrophobicity, and local flexibility using well‐known thermostable model systems such as the villin headpiece subdomain (HP36) and the third immunoglobulin G‐binding domain of protein G (GB3). Reversed‐phase high‐performance liquid chromatography (RP‐HPLC) measurements as a function of temperature probe global thermal stability in the presence of acetonitrile, while differential scanning calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Biophysical characterization of both D-HEWL variants and commercially available unlabelled HEWL shows that both D-HEWL molecules are stable and active. The perdeuterated variants showed lower thermal stability relative to the hydrogenated protein both in D 2 O and H 2 O buffers, in line with what has been reported in several biophysical studies on protein deuteration (Berns, 1963;Hattori et al, 1965;Brockwell et al, 2001;Meilleur et al, 2004;Koruza et al, 2018;Nichols et al, 2020). Additionally, it seems that both hydrogenated and perdeuterated forms of HEWL have an increased transition temperature in D 2 O compared with H 2 O, as described in previous studies (Makhatadze et al, 1995;Efimova et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Biophysical characterization of both D-HEWL variants and commercially available unlabelled HEWL shows that both D-HEWL molecules are stable and active. The perdeuterated variants showed lower thermal stability relative to the hydrogenated protein both in D 2 O and H 2 O buffers, in line with what has been reported in several biophysical studies on protein deuteration (Berns, 1963;Hattori et al, 1965;Brockwell et al, 2001;Meilleur et al, 2004;Koruza et al, 2018;Nichols et al, 2020). Additionally, it seems that both hydrogenated and perdeuterated forms of HEWL have an increased transition temperature in D 2 O compared with H 2 O, as described in previous studies (Makhatadze et al, 1995;Efimova et al, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Surprisingly, the observations suggest that in vitro refolding has a stronger impact on HEWL thermal stability than protein perdeuteration, with the respective decreases in T m being greater than 3.5 C compared with variations of smaller than 1.6 C. These changes in HEWL thermal stability are consistent throughout different buffer compositions and also in H 2 O and D 2 O solvents, where the minor deviations can be explained by the aforementioned difference between pH and pD (Glasoe & Long, 1960). Moreover, the reduction in protein thermal stability associated with protein perdeuteration is in agreement with several previous studies (Berns, 1963;Hattori et al, 1965;Brockwell et al, 2001;Meilleur et al, 2004;Koruza et al, 2018;Nichols et al, 2020;Ramos et al, 2021).…”
Section: Deuteration and In Vitro Refolding Differently Affect The Biophysical Properties Of Hewlsupporting
confidence: 91%
“…While hydrogenated and perdeuterated variants of a protein are usually close to identical in structure, several studies of the macromolecular H/D isotope effect have reported decreases in the thermal stability of perdeuterated proteins compared with their hydrogenated analogs (Berns, 1963;Hattori et al, 1965;Brockwell et al, 2001;Meilleur et al, 2004;Koruza et al, 2018;Nichols et al, 2020;Ramos et al, 2021). Observations have also been made regarding solvent H/D isotope effects which suggest that both perdeuterated and hydrogenated proteins are thermally more stable in D 2 O than in H 2 O (Hattori et al, 1965;Harrington & von Hippel, 1961;Makhatadze et al, 1995;Freyman et al, 2001;Kuhlman & Raleigh, 1998;Sasisanker et al, 2004;Efimova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the deuteration of non-exchangeable protons in globular proteins was found to reduce their denaturation temperature of few degrees [48,49,50],…”
Section: Swelling Behaviour Of Pnipam Microgelsmentioning
confidence: 97%